2018
DOI: 10.1590/1982-0194201800002
|View full text |Cite
|
Sign up to set email alerts
|

Análise do uso de um sistema informatizado por gestores hospitalares

Abstract: Resumo Objetivo: Analisar o uso de um sistema informatizado pelos gestores hospitalares, avaliando a satisfação quanto à utilidade e facilidade de uso do sistema. Métodos: Estudo de caso, com delineamento não experimental, realizado em um hospital geral. Utilizou-se um instrumento baseado no modelo de aceitação tecnológica. A população foi composta por 63 gestores, de acordo com os critérios de inclusão, 60 gestores compuseram a amostra do estudo. Resultados: No total, 90,5% dos gestores concordaram com a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
2
0
4
Order By: Relevance
“…The ease of using technology is a factor that influences its acceptance, since people with better computer skills manipulate technological tools more easily. 12 Positive aspects evolved in the questions about the ease of use of EMR, as they showed greater agreement, while the questions that emphasized the difficulty with the use of the system presented intermediate or discordant values. Consistency in completing and completing the survey by respondents, as well as acceptance of the ease of use of technology in the group of stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…The ease of using technology is a factor that influences its acceptance, since people with better computer skills manipulate technological tools more easily. 12 Positive aspects evolved in the questions about the ease of use of EMR, as they showed greater agreement, while the questions that emphasized the difficulty with the use of the system presented intermediate or discordant values. Consistency in completing and completing the survey by respondents, as well as acceptance of the ease of use of technology in the group of stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Para adesão dos profissionais ao uso da ferramenta, pontos chaves recomendados pela literatura foram considerados, como a apresentação dos dados que deve ser clara e concisa, a linguagem de fácil compreensão, o tempo de preenchimento e o conhecimento da equipe quanto a utilização do dados obtidos após o preenchimento do instrumento 9,11 . Os profissionais de enfermagem são os principais profissionais da saúde a manusearem os sistemas informatizados hospitalares, assim o treinamento é essencial, com atenção a alta rotatividade de profissionais, assim como deve ter o objetivo de sanar dúvidas e validar o conhecimento junto a especialistas, periodicamente 8,11,14 .…”
Section: Discussionunclassified
“…The ease of using a technology influences its acceptance. One study found that being able to manipulate technological tools influences the use of a HIS (21) . Thus, conducting information system training is related to the ease of use and usefulness of the system as it enhances people's ability to handle the technology (19,21) .…”
Section: Discussionmentioning
confidence: 99%